Remoção de nitrogênio ou fósforo presente em efluentes agroindustriais pela precipitação de estruvita - Santos, Wilson Roberto Barreto dos (2011)
Given the potential of the use of physical-chemical process in wastewater treatment, this project aimed to study the reduction of phosphorus and / or nitrogen present in effluents and liquid manure from pigs, meat slaughter of cattle (bovine blood) and disposal of refrigerants. The technology used in the removal of ammonia and phosphorus is its precipitation in the form of struvite (Mg (NH4) PO4.6H2O). To enable the precipitation of ammonia and phosphorus as struvite, is necessary the presence of the participants such as Mg, which will be supplied by the addition of phosphoric acid, potassium phosphate, magnesium hydroxide, magnesium oxide and ammonium chloride concentrations varied. These concentrations were added in 2.0- liter beakers and kept under agitation using a jar-test equipment. Then the samples were filtered and the precipitates were analyzed by diffraction and X-ray. The supernatant was analyzed seen a removal of nitrogen and phosphorus above 80%. The removal of these components depends on the type of effluent tested. Nitrogen and phosphorus precipitated as struvite, can be used in the formulation of fertilizer with slow release of these elements.